PENELITIAN PENGARUH MARKET ORIENTATION TERHADAP CUSTOMER LOYALTY XL AXIATA DI SURABAYA DENGAN MARKETING CAPABILITY DAN COMPETITIVE ADVANTAGE SEBAGAI VARIABEL INTERVENING - christian ganadhi the (Jurnal Strategi Pemasaran, 2016)
The development of mobile phone users in Surabaya experiencing very rapid growth. With the development of the telecommunication companies competing to win the market competition. This study aims to analyze the influence of the Market Orientation of the Customer Loyalty in Surabaya Xl Axiata with a Marketing Capability and Competitive Advantage as a variable intervening. This study will be conducted by distributing questionnaires to 100 respondents which are customers of XL Axiata in Surabaya. Analysis technique used is quantitative analysis techniques with path analysis method